Representing the Reprehensible: Fairy Tales, News Stories & the Monstrous Karla Homolka - Smith Fullerton, Romayne (Atlantis, 2006)
Fairy tales and news stories are not often linked; however, in many news stories, Canadian media depicted Karla Homolka as both passive princess and evil witch. This paper argues journalists used aspects of popularized fairy tales to shape and give meaning to Homolka's life, personality and crimes, and these constructs created a discourse that limited, liberated and ultimately problematised the public's conception of Homolka.